PENYERBUKAN PADA RAMBUTAN (NEPHEUUM LAPPACEUM L. VAR. LAPPACEUM) - UJI, TAHAN (Research Center for Biology-Indonesian Institute of Sciences, 1987)
TAHAN UJI.1987.Pollination in Nephelium lappaceum L. var.lappaceum. Suppl.Berita Biologi. 3 : 31 - 34.Inflorescence morphology,flowering biology and insect visitors of rambutan (Nephelium lappaceum L. var.lappaceum) were observed in Semboja, East Kalimantan.Rambutan is dioeceous plant and cross pollinated by insect.It was showed that in isolated inflorescence failed to produce fruits.Six species of bees i.e. Apisindica,Trigone itama,T. nitidiventris. T. canifronsT.irridipenis and T.atripes are potential for their pollinators.